The role of faith in parenting; considerations when implementing family skills interventions with families affected by armed conflict or displacement - El-Khani, Aala; Calam, Rachel; Maalouf, Wadih (Frontiers in Psychiatry, 2023)
Religious beliefs and practices are fundamental to shaping family functioning in many countries and cultures around the world. They are often associated with a strong influence on parenting, and a potential resource for parents. While nurturing caregiving can act as a protective shield, buffering against the negative effects on children’s well-being, armed conflict and displacement often compromises parental well-being and positive parenting practices. Making interventions available to families affected by conflict and displacement that help to develop the quality of parenting is now seen as an important component in the care of war-affected children, causing a rise in family skills interventions for humanitarian contexts. Accordingly, there are certain considerations that need to be taken to achieve cultural sensitivity and acceptability, that account for the influence of religion. Here we share our United Nations Office on Drugs and Crime (UNODC) experience in the case of implementing “Strong Families,” a UNODC family skills programme implemented in over 30 countries, providing key recommendations. (1) Appreciate and account for common religious beliefs and practices in your target populations; (2) ensure programme material acceptability and sensitivity; (3) avoid initiation of direct discussions, on religious beliefs or practices; and (4) facilitator need to be trained and prepared to respond to questions about faith. Though these considerations are presented considering the implementation of family skills programmes, they are also relevant to a range of other programming in which direct social (or other) contact is made with families in challenged contexts, aiming to reduce any perceived gaps between trainers and the families they are working with, and give families a sense that their religious beliefs, values, and priorities are understood.